Design of a Solar Powered Water Supply System for Kagadi Model Primary School in Uganda - Uche, Chikadibia Kalu Awa; Udoka, Eza Val Hyginus; Kisakye, Abigaba; Maxwell, Kugonza Francis; Wisdom, Okafor O. (Journal of Engineering, Technology, and Applied Science (JETAS), 2023)
The presence of water is a prerequisite condition for the existence and sustainability of life on the planet. Adequate supply of clean water is even more significant for a primary school as it ensures hydration, sanitation, hygiene leading to a general wellbeing of the pupils. This research work successful designed a solar powered water supply system for Kagadi Model Primary School (KMPS) and its environs. The research design takes into account the population of the students, total daily water demand, water source potential in terms of quality and quantity and insolation potential of the study area which formed the bed bedrock of the suitable location of the designed system. This developed system will help to distribute water fairly to the KMPS and its environ at very a cheap and steady manner for the pump will be powered with solar energy. The solar water pump will be energized using solar energy system to pump water into the storage facility (reservoir) before distributing it by the help of gravitational force to various locations for consumption. This designed solar powered energy system when implemented will curb the problem of water scarcity, provide clean water and reduce unhygienic nature of the environment as it in line with Sustainable Development Goals (SDGs). This study recommends the implementation of this design to provide clean and steady water supply for the residents of the study area.